運動時間の非設定が有酸素性運動時に自己選択される強度レベルに及ぼす影響 - 沼尾, 成晴; 田中, 喜代次; 中垣内, 真樹; 荒井, 弘和; 林, 容市 (体育学研究, 2008)
The use of self-selected exercise intensity (SS) is reported to simplify the prescription of exercise and enhance exercise adherence. However, the specific duration of aerobic exercise necessary to achieve improvements in fitness when using self-selected exercise intensity levels remains undetermined. The purpose of this study was to examine the effect of self-selected exercise duration on the level of exercise freely selected by the subject. Nine healthy men (mean±SD, 27.8±2.4 years) performed two trials. In the first trial, the subjects performed 20 minutes of cycling using the SS trial. In the other trial, the subjects selected both an exercise intensity and duration (SS-T trial). There was no significant difference between the intensity selected during the SS and SS-T trials (SS trial: 54.3±8.9% VO2max, SS-T trial: 56.0±10.5% VO2max). Also, there was no difference in several psychological indices between the two trials. However, during the SS-T trial only 4 subjects exercised for more than 20 minutes, the recommended minimum duration for aerobic exercise. The average of VO2max selected during the SS trial was significantly correlated with VO2max for each subject (r=0.70). These data suggest that SS in combination with an assigned exercise duration is more effective than self-selecting both the intensity and duration in order to achieve the recommended levels of exercise activity.